1997
DOI: 10.1007/s002709900188
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Gastric and Duodenal Stenosis: Palliation by Peroral Implantation of a Self-Expanding Metallic Stent

Abstract: Implantation of stents resulted in palliative relief of malignant antrum-pylorus-duodenal obstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 13 publications
1
39
1
Order By: Relevance
“…Tumor ingrowth occurred in 14 (26.4%) patients at a mean of 78.4 d in our study. Overall recurrent stenosis rates of 8%-46% at an interval of 2-21 wk (mean, 7.5 wk) have been reported in other studies [14,15,[19][20][21][22][23][24] . It is difficult to compare our results with results of other studies because other reports included patients with a variety of cancers.…”
Section: Discussionmentioning
confidence: 56%
“…Tumor ingrowth occurred in 14 (26.4%) patients at a mean of 78.4 d in our study. Overall recurrent stenosis rates of 8%-46% at an interval of 2-21 wk (mean, 7.5 wk) have been reported in other studies [14,15,[19][20][21][22][23][24] . It is difficult to compare our results with results of other studies because other reports included patients with a variety of cancers.…”
Section: Discussionmentioning
confidence: 56%
“…Although the experience is still early and most series are small, the rate of success for the placements of gastroduodenal stents has been very good. In some series, the technical success for stent deployment has been reported to be as high as 100% [3,15,19]. The largest series [20] reports a 93.5% success rate with the placement of 31 stents in 29 patients.…”
Section: Discussionmentioning
confidence: 96%
“…Median survival rates in other studies ranged from 7 to 141 days after stent placement and from 70 to 249 days after GJJ [1,4,8,15,16,19,20,[25][26][27]. Previous studies have suggested that survival rates were higher after GJJ than after stent placement.…”
Section: Gjj Stentmentioning
confidence: 96%